Estratégias de adaptação para o conforto térmico em ambiente escolar: um estudo em escolas públicas de Porto Nacional – TO. - REIS, Matheus da Silva (Universidade Federal do Tocantins, 2023)
This article aims to address the adaptation strategies for thermal comfort in state schools of basic education in Porto Nacional - TO. The main parameters for the research were defined after an interview given by architect Hellen Goulart, from SEDUC/Tocantins. From this interview, it was possible to list aspects for observation in the selected schools, as well as a set of questions to be raised with the managers of these schools. Thus, information was obtained about the structure of the school building, its free areas, afforestation, strategies used to deal with heat and complaints from the school community about discomfort situations, considering the usual high temperatures in Porto Nacional. The selected schools were: Costa e Silva State School, Felix Camôa High School and Alcides Rodrigues Aires. With the results it was possible to establish some points that contribute negatively and positively to the thermal contortion of schools, seeking dialogue with authors who address the theme and with the role of Geography for a critical reading of the relations between nature (such as climate) and the constructed space (such as the school and its facilities). In addition, the research aimed to contribute to a sensitive theme that should be discussed in the academic sphere, of SEDUC/Tocantins itself and the school community, including managers, teachers, students and parents. The purpose is to arrive at solutions to the frequent situations of thermal discomfort in schools, in order to ensure the necessary conditions for the good school performance of students and good working conditions for teachers and other employees.